PEDAGOGICAL METHODOLOGY AND DEVELOPMENT INCLUSIVE IMAGERY AND CONTEXT INTEGRATION SCIENCE, OBSHCHESTVA AND IMAGERY (Universal International Scientific Journal, 2026)
This article examines the current pedagogical conditions for the implementation and development of inclusive education within the framework of integrating science, society, and the education system. Particular attention is paid to teacher training, the use of digital technologies, the creation of an accessible educational environment, and the development of a tolerant attitude toward students with special educational needs. Inclusion is interpreted as a socio-pedagogical process aimed at equal opportunities for all participants in the educational process.
Keywords: inclusive education, pedagogical conditions, integration, accessible environment, tolerance, digitalization, equal opportunities, social development, competence, socialization